Mesofauna y calidad del suelo en Agrosistemas Zungarococha Loreto 2024 - Vargas Fasabi, Jorge Aquiles (2025)
The objective of the study was to evaluate soil quality in productive systems based on the relationship between macrofauna composition and physicochemical factors (pH, aluminum saturation and organic matter) in five systems: agricultural (cassava), pasture, citrus, primary forest and agroforestry (SAF) in Zungarococha, Loreto, Peru. Sampling of soil macroinvertebrates, both leaf litter and soil engineers (earthworms, termites and ants), was carried out in plots of each production system. Physical-chemical analyses were carried out to determine organic matter content, pH and cation exchange capacity. In the laboratory, macrofauna were separated and counted for taxonomic analysis and proportions of detritivorous and non-detritivorous organisms were calculated as indicators of decomposition and nutrient recycling activity. The results indicated that the agricultural system had low soil quality, with a pH of 4.0 and 95.95% aluminum saturation, in addition to a low diversity of macrofauna, which limits decomposition. In contrast, the primary forest showed moderate-high quality and high biodiversity (48.1% termites), despite acidic conditions (pH 3.7 and 77.82% aluminum saturation). The agroforestry and pasture systems had moderate soil quality, with balanced decomposition activity and organic matter levels of 2.69%. This study shows that the monitoring of macrofauna and physicochemical factors is essential for sustainable soil management in productive systems. It is essential to improve the agricultural system to increase its biodiversity and nutrient recycling capacity, which will promote its fertility and long-term sustainability.